Automatic Cardiopulmonary Resuscitation System - Rawin Keakultanes; May Phu Paing; Chuchart Pintavirooj (My University, 2022)
Cardiac arrest occurs when the heart unexpectedly malfunctions and stops breathing and pumping blood. Cardiopulmonary resuscitation, an emergency resuscitation procedure, must be performed as soon as possible when the patients suffer cardiac arrest to prevent brain damage or stop breathing. If not, it may lead a person dead even in a short time (from 8-10 minutes) of cardiac arrest. According to the American Heart Association, proper CPR must be performed at a depth of 5 cm in the sternum and a rate of chest compressions of 100 to 120 breaths per minute. Therefore, medical personnel or the person who performs CPR must be well-trained to conduct proper CPR. For this reason, CPR machines are demanded to assist and support medical personnel in saving human lives. This paper will focus on developing an automated CPR machine and automatic resuscitation ventilator to ensure that patients receive proper CPR. The device will be wirelessly controlled by a mobile phone via Bluetooth and was able to press at a depth of 4-5 cm, which is a correct depth, and at a rate of 70 beats per minute. An Arduino Uno microcontroller and a linear motor are used to control the push of the device. The proposed automated CPR machine will be a cost-effective, fully functional CPR device that is easy to use and can help people or healthcare professionals perform proper CPR.
Keywords: Cardiac Arrest and Resuscitation; Respiratory Support and Mechanisms; Mechanical Circulatory Support Devices